Jump Rope Play Therapy to Enhance Social Interaction in a Child with Gadget Addiction: A Case Study - Renata Syaira Hasbillah; Andan Firmansyah; Dadi Hamdani (KIAN JOURNAL, 2026)
Introduction: Excessive gadget use among school-age children has become a growing concern due to its negative impact on social and behavioral development. Children who spend prolonged periods using digital devices often exhibit reduced social engagement, limited verbal communication, emotional withdrawal, and decreased participation in peer interactions. These conditions may hinder the development of essential interpersonal skills during a critical stage of growth. Traditional play activities, such as jump rope, offer opportunities for physical movement, communication, cooperation, and social interaction, making them potential therapeutic interventions for children experiencing gadget-related social difficulties. Objective: This study aimed to evaluate the effectiveness of jump rope play therapy in improving social interaction among children with gadget addiction. Method: A descriptive case study design was employed involving a 10-year-old female child residing in Dayeuhmanggung Village, West Java, Indonesia. The intervention consisted of two structured jump rope play therapy sessions conducted over four consecutive days. Data were collected through semi-structured interviews with parents, direct observations using behavioral checklists, gadget usage logs, and field documentation. Behavioral changes before and after the intervention were analyzed descriptively. Results: Following the intervention, the child demonstrated notable improvements in social behavior. Daily gadget use decreased from more than 3 hours to approximately 1.5 hours. Increased eye contact, spontaneous verbal responses, initiation of conversations, active participation in outdoor play, and greater willingness to interact with family members and peers were observed. Parents also reported enhanced sociability, improved mood, and reduced dependence on digital devices. Conclusion: Jump rope play therapy appears to be a culturally appropriate, low-cost, and effective intervention for enhancing social interaction and reducing gadget dependency among school-age children. The findings suggest that integrating traditional play activities into community and family-based nursing interventions may support children's psychosocial development and social reintegration.